Participating for Profit: Bilateral-Multilateral Nexus in Indonesian Foreign Policy in the Era of Joko Widodo (2014-2019) - Rosyidin, Mohamad; Kusumawardhana, Indra (Political Science Program, Universitas Negeri Semarang, 2022)
This paper seeks to analyze Indonesia’s multilateral diplomacy under President Joko Widodo (Jokowi)during his first term of presidency(2014-2019). Specifically, this research will be focusing on threemultilateral forums; G20, APEC, and East Asia Summit. Thispaper departs from the puzzle of why Jokowi’s foreign policy seems to be paradoxical; on one hand, the bilateral approach looks very prominent but on the other, Jokowi does not seem to be very keen in engaging in multilateral forums. Using bilateral-multilateral nexus, this paper argues that Indonesia’s participation in multilateral forums is only intended as a means of pursuing short-term interests rather than to contributing to global norms. Jokowi uses multilateralism just as a venue to arrange further bilateral cooperation with potential partners.